EFFECT OF HYDROTHERMAL TREATMENT DURATION ON THE PHOTOCATALYTIC PERFORMANCE OF ZINC OXIDE (ZNO) NANORODS FOR WASTEWATER PURIFICATION: PENGARUH LAMA PERLAKUAN HIDROTERMAL TERHADAP KINERJA FOTOKATALIK ZINC OXIDE (ZNO) NANORODS UNTUK PEMURNIAN AIR LIMBAH - Muhammad Fajar Setiawan; Iwan Sugihartono; Nurfina Yudasari (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
Zinc Oxide (ZnO) has been extensively developed in the field of wastewater treatment as a photocatalyst to degrade dye contaminants. The photocatalytic efficiency of ZnO can be enhanced by modifying its nanostructure, particularly by synthesizing ZnO in the form of nanorods. In this study, a simple hydrothermal method was used to synthesize ZnO nanorods and evaluate their effectiveness in degrading textile dye wastewater, using rhodamine B (RhB) and methylene blue (MB) as model pollutants. Zinc sheets with a thickness of 0.1 mm were treated hydrothermally in an autoclave containing 50 ml of deionized water at 95°C for 8, 16, and 24 hours. Subsequently, each sample was analyzed for its morphological and structural characteristics before being immersed in RhB and MB solutions with a concentration of 5 ppm and exposed to UV light at a wavelength of 352 nm and an intensity of 900–1000 mW/cm2. The degradation rates of RhB were found to be 63.4% for ZnO-8, 94% for ZnO-16, and 79.9% for ZnO-24, while for MB, they were 74.3% for ZnO-8, 75% for ZnO-16, and 68% for ZnO-24. These results indicate that ZnO synthesized hydrothermally for 16 hours exhibited superior degradation performance for both rhodamine B and methylene blue compared to the 8-hour and 24-hour treatments.